Intelligent System for Automated G-Code Generation: Development and Validation of STEP File Integration in CNC Machining - Abd Rahman, Zammeri; Mohamed, Saiful Bahri; Kasim, Mohd Shahir; Minhat, Mohamad; Rohimi, Razwan; Md Sharizam, Muhammad Abdulrahim Rabbani; Tengku Sulaiman, Tengku Mohd Sharir; Abd Rahman, Zulkifli (International Journal of Integrated Engineering, 2026)
The integration of Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) remains critical in automating tool path generation for CNC machining. However, interoperability issues and reliance on proprietary CAM systems impede small-scale manufacturing efficiency. This study presents an Integrated Interface System (IIS) that directly converts STEP file geometric data into G-code, eliminating the need for intermediary CAM software. Developed using PHP, the IIS extracts and interprets critical geometric entities such as EDGE_LOOP, ORIENTED_EDGE, and CARTESIAN_POINT from the STEP file to generate precise machining tool paths. Validation was performed by comparing the G-code output from IIS with SolidCAM-generated results using CNC Simulator software. Results demonstrated that IIS produces identical tool path accuracy and machining profiles with reduced complexity and cost. A case study confirmed the system’s reliability in generating both linear and circular tool paths for a 3-axis CNC milling machine, achieving precision machining with a 10 mm depth of cut. The proposed system addresses the gaps in STEP-based G-code automation, streamlining tool path generation and offering a cost-effective, scalable solution for small-to-medium CNC operations. Future work will focus on expanding compatibility for multiple-axis machining and improving feature recognition algorithms.